Salt, kidney and hypertension - Salas Z, Aníbal (2006)
Aníbal Salas, Carlos Battilana Life in the species evolution when migrating from water to earth developed various adaptative mechanisms for salt regulation. The most important is the currently known yuxtaglomerular system. Diverse pathophysiologic mechanisms are implicated in arterial hypertensionpathogenesis, including enzymatic interaction between WNK1 and SGK1 enzymes, yuxtaglomerular apparatus imbalance, angiotensin II overexcitability, pressure natriuresis, genetic factors recently studied like 11 ß-hydroxysteroid dehydrogenase enzyme gen mutation, aberrant tubular glomerular balance in relation to salt intake, and nephronal subdonor theory. Finally, the close relationship between the metabolic syndrome and arterial hypertension has opened a new horizon on arterial hypertension diagnosis and treatment. All these mechanisms have led to diverse clinical expressions, determining the concept of salt sensitive persons and the importance of low salt diet.